Intravital Microscopy of the Beating Murine Heart to Understand Cardiac Leukocyte Dynamics - Allan-Rahill, Nathaniel H.; Lamont, Michael R. E.; Chilian, William M.; Nishimura, Nozomi; Small, David M. (Frontiers in Immunology, 2020)
Cardiovascular disease is the leading cause of worldwide mortality. Intravital microscopy has provided unprecedented insight into leukocyte biology by enabling the visualization of dynamic responses within living organ systems at the cell-scale. The heart presents a uniquely dynamic microenvironment driven by periodic, synchronous electrical conduction leading to rhythmic contractions of cardiomyocytes, and phasic coronary blood flow. In addition to functions shared throughout the body, immune cells have specific functions in the heart including tissue-resident macrophage-facilitated electrical conduction, and rapid monocyte infiltration upon injury. Leukocyte responses to cardiac pathologies, including myocardial infarction and heart failure, have been well-studied using standard techniques, however, leave certain questions related to spatiotemporal relationships unanswered. Intravital imaging techniques could greatly benefit our understanding of the complexities of in vivo leukocyte behavior within cardiac tissue, but these techniques have been challenging to apply. Different approaches have been developed including high frame rate imaging of the beating heart, explantation models, micro-endoscopy, and mechanical stabilization coupled with various acquisition schemes to overcome challenges specific to the heart. The field of cardiac science has only begun to benefit from intravital microscopy techniques. The current focused review presents an overview of leukocyte responses in the heart, recent developments in intravital microscopy for the murine heart, and a discussion of future developments and applications for cardiovascular immunology.